Testing of nickel-chrome alloy as a tip material for multi-tip langmuir probes - Naz, M.Y. (World Scientific Publishing Co. Pte Ltd, 2014)
The electrostatic probes are considered to be the most powerful and experimentally simplest technique for plasma characterization. The objective of the work was to test the nickel-chrome alloy as probe tip material for characterization of RF discharge plasmas. In order to meet the objective, a triple Langmuir probe diagnostic system and associated driving circuit was designed and tested in inductively coupled plasma (ICP) generated by a 13.56 MHz radio frequency (RF) source. Using this probe diagnostic, the electron temperature, electron number density and ion saturation current were measured as a function of input RF power and filling gas pressure. An increasing trend was noticed in electron temperature and electron number density with input power whilst a decreasing trend was evident in these parameters for increasing nitrogen gas pressure. The overall variations in electron temperature and electron number density after repeated measurements were ranging from 5 to 12 and 3 to 13, respectively. Â© 2014 World Scientific Publishing Company.